Visual Basic .Net Programming with Peter Aitken. - Aitken, Peter; Biafore, Bonnie (Paraglyph Press [Imprint] Paraglyph, Inc. Ingram Publisher Services [distributor], 2001)
Annotation Features a logical and understandable approach aimed at beginner to intermediate level programmers. Numerous real-world programming examples are included and special coverage of topics such as object-oriented programming, error-handling, graphics, debugging, and .Net programming techniques are provided. It walks the reader through the creation of three databases: a simple flat file database, a very simple relational database, and a more complex relational database.